Sirtuins, Metabolism, and Cancer - Martinez-Pastor, Barbara; Mostoslavsky, Raul (Frontiers in Pharmacology, 2012)
More than a decade ago, sirtuins were discovered as a highly conserved family of NAD+-dependent enzymes that extend lifespan in lower organisms. In mammals, sirtuins are key regulators of stress responses and metabolism, influencing a range of diseases, including diabetes, neurodegeneration and cancer. In recent years, new functions of sirtuins have been characterized, uncovering the underlying mechanisms of their multifaceted role in metabolism. Here, we specifically review recent progress on the role of sirtuins in DNA repair and energy metabolism, further discussing the implication of sirtuins in the biology of cancer.